Students’ Prior Knowledge and Skills in Computer and Internet Use: An Exploration of Incoming First Year Undergraduate Health Sciences Students at Gulu University, Uganda - Yagos, Onen Walter; Tabo-Olok, Geoffrey; Ovuga, Emilio (Journal of Health Information and Librarianship, 2020)
Internet has provided infrastructure that enables access to a variety of information resources for use by medical students at Gulu University in Northern Uganda. However, little attention has been put to explore prior internet knowledge of undergraduate medical students in Uganda. Cross-sectional research design was used. Fifty-six first year undergraduate health sciences students participated in the study. Self-administered structured questionnaire was used for data collection and analysis was done using SPSS version 16. Results shows that a majority of the participants had prior knowledge of computer 48 (86.0%) and internet 44 (79.0%). 38 (68.0%) participants had access to internet and 34 (61.0%) owned computer before joining the University. Majority owned mobile phones 41 (73.0%) and used it for internet access 43 (84.0%). Use of internet was high in social media 46 (86.8) and searching general information 44 (84.6%). Participants expected easy access to teaching materials 52 (94.5%) and communication 49 (90.7%) via internet. These findings suggest need for healthcare librarians to train incoming medical students on use of ICTs; including social media platforms and mobile phones to improve their ICT literacy skills to enable them access the best academic information resources to enhance medical education.
Keywords: Internet skills; Gulu University; First year health sciences students; Uganda